2013
DOI: 10.1021/bi400264d
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Galactopyranose Mutase in Nematodes

Abstract: Nematodes represent a diverse phylum of both free living and parasitic species. While the species Caenorhabditis elegans (C. elegans) is a valuable model organism, parasitic nematodes or helminths pose a serious threat to human health. Indeed, helminths cause many neglected tropical diseases that afflict humans. Nematode glycoconjugates have been implicated in evasive immunomodulation, a hallmark of nematode infections. One monosaccharide residue present in the glycoconjugates of several human pathogens is gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 66 publications
(160 reference statements)
2
30
0
Order By: Relevance
“…3. Comparison with available data from the other eukaryotic UGMs show that, although there are minor differences between the k cat and K m values, the catalytic efficiencies ( k cat / K m ) are very similar among all eukaryotic enzymes, with the exception of A. fumigatus UGM (Table 1) [18, 19, 27]. …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…3. Comparison with available data from the other eukaryotic UGMs show that, although there are minor differences between the k cat and K m values, the catalytic efficiencies ( k cat / K m ) are very similar among all eukaryotic enzymes, with the exception of A. fumigatus UGM (Table 1) [18, 19, 27]. …”
Section: Resultsmentioning
confidence: 97%
“…It has been shown that in the reduced form, the FAD-N5 attacks the UDP-Gal p at the C1 position, leading to breaking of the anomeric bond and formation of an FAD-galactose adduct. This adduct is essential for sugar ring contraction [9, 14, 27, 31]. Recently, we showed that Tc UGM and Af UGM can be reduced by NADPH and to a lesser extent by NADH [14].…”
Section: Resultsmentioning
confidence: 99%
“…Because Gal f is absent in human [44], UGM has been used as a desirable drug target [49]. UGM coded by gene GLF was later found in several eukaryotic unicellular pathogens [50] as well as in nematodes [51]. Can we repurposing drugs developed against bacterial pathogens to fight eukaryotic unicellular pathogens [50]?…”
Section: Human Diseases Caused By Pathogensmentioning
confidence: 99%
“…7, 8 Although Gal f -containing glycans in nematodes have yet to be identified, nematodes encode a UGM, and Caenorhabditis elegans expresses a functional UGM. 9-11 In contrast, Gal f residues are not found in mammals nor do mammals possess UGM. 12 In many organisms that encode a UGM, deletion or downregulation of UGM production has deleterious consequences, 9, 13 including lethality in mycobacteria.…”
Section: Introductionmentioning
confidence: 97%